Patients with penile cancer and the risk of (pre)malignant cervical lesions in female partners: a retrospective cohort analysis. (26th July 2013) - de, Roderick E.; Heideman, Danielle A.M.; Kenter, Gemma G.; van, Marc; van, Harm; Horenblas, Simon
<x xml:space="preserve">Abstract</x> Objective To determine if female partners of patients with penile cancer have more cervical lesions and neoplasia than would be expected from population‐based data. Patients and Methods We included all consecutive patients with primary penile carcinoma in the period 2004–2010. Results of Dutch cervical cancer screening were used to consider (pre)malignant cervical lesions in female partners of patients with penile cancer. Results In all, 206 women were included. Gynaecological information was available in 195 women: Papanicolaou test (PAP) smears were normal were in 129 partners, 10 smears were abnormal (5.1%, 95% confidence interval 2.5–9.2). PAP2 was found in five, PAP3a in two, PAP3b in two women and PAP4 in one woman. Colposcopy in two women with PAP3b showed cervical intraepithelial neoplasia grade 3 in both. This prevalence was not different from baseline results in the general Dutch population. Conclusion Female partners of patients with penile cancer did not show more premalignant cervical lesions than in the general population.